The evolution of the January effect - Moller, Nicholas; Zilca, Shlomo (Journal of Banking & Finance, 2008)
This paper extends recent studies of the January effect by investigating the evolution of the daily pattern of the effect across size deciles. Our evidence documents a sizable mean reverting component beginning in the latter part of January and a shorter duration of the seasonal effect. Despite lower abnormal returns in the second part of January, higher abnormal returns in the first part of January keep the magnitude of the January effect unchanged. Further analysis of daily trading volumes suggests a stable trading volume intensity in the first part of January and a substantial decline in trading volume intensity in the second part of January.